2007
DOI: 10.1016/j.jacc.2006.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Collagen and Smooth Muscle Cell Content in Atherosclerotic Plaques Using Polarization-Sensitive Optical Coherence Tomography

Abstract: Our results demonstrate that PSOCT enables the measurement of birefringence in plaques and in fibrous caps of necrotic core fibroatheromas. Given its potential to evaluate collagen content, collagen fiber thickness, and SMC density, we anticipate that PSOCT will significantly improve our ability to evaluate plaque stability in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(141 citation statements)
references
References 28 publications
5
132
0
2
Order By: Relevance
“…In NCFAs, PSOCT birefringence highly correlated with collagen content of fibrous caps, potentially providing an important indicator of plaque stability. A strong positive correlation was demonstrated between PSOCT birefringence and thick collagen fiber content (R=0.76, P<0.0001) [37] These results may be influenced by other sources of birefringence due to the compositional heterogeneity in atherosclerotic plaques, such as the presence of cholesterol crystals and SMCs. PSOCT birefringence demonstrated a high correlation with SMC content (R=0.74, P<0.0001) [37].…”
Section: Polarization-sensitive Octmentioning
confidence: 82%
See 2 more Smart Citations
“…In NCFAs, PSOCT birefringence highly correlated with collagen content of fibrous caps, potentially providing an important indicator of plaque stability. A strong positive correlation was demonstrated between PSOCT birefringence and thick collagen fiber content (R=0.76, P<0.0001) [37] These results may be influenced by other sources of birefringence due to the compositional heterogeneity in atherosclerotic plaques, such as the presence of cholesterol crystals and SMCs. PSOCT birefringence demonstrated a high correlation with SMC content (R=0.74, P<0.0001) [37].…”
Section: Polarization-sensitive Octmentioning
confidence: 82%
“…A strong positive correlation was demonstrated between PSOCT birefringence and thick collagen fiber content (R=0.76, P<0.0001) [37] These results may be influenced by other sources of birefringence due to the compositional heterogeneity in atherosclerotic plaques, such as the presence of cholesterol crystals and SMCs. PSOCT birefringence demonstrated a high correlation with SMC content (R=0.74, P<0.0001) [37]. Further analysis of PSOCT images may allow a more precise determination of collagen content to be made.…”
Section: Polarization-sensitive Octmentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, the identification of organized collagen fiber in arteries has also been demonstrated by using a single-detector PS-OCT (Giattina et al, 2006). In addition, another report showed that the PS-OCT measurements of birefringence have a strong positive correlation with thick collagen fiber content (r = 0.76, p < 0.001) and also a smooth muscle cells density (r = 0.74, p < 0.01) (Nadkarni et al, 2007).…”
Section: Fig 6 Histological and Ps-oct Images Of Fibrocalcific Plaqmentioning
confidence: 94%
“…OCT can quantify typical characteristics such as the fibrous cap thickness [182], presence of lipid [135], or macrophage infiltration [183]. The degradation of organized collagen fibers can be detected with PS-OCT [84,184], and extraction of local attenuation coefficients enables the automated identification of different tissue structures [137]. With these capabilities of highresolution intravascular imaging and extraction of information about the tissue composition, OCT has become a valuable research tool for studying cardiovascular diseases [185][186][187] and possible treatments [188].…”
Section: Cardiologymentioning
confidence: 99%